Magnetostratigraphic dating of the Shanshenmiaozui mammalian fauna in the Nihewan Basin, North China. (2nd May 2016) - Liu, Ping; Wu, Zhijun; Deng, Chenglong; Tong, Haowen; Qin, Huafeng; Li, Shihu; Yuan, Baoyin; Zhu, Rixiang
Abstract: Timing of the mammalian faunas in the Nihewan Basin, North China has provided insights into our understanding of Quaternary biochronology and biostratigraphy in East Asia. Here we contribute to this topic with detailed magnetostratigraphic investigation, coupled with mineral magnetic measurements on a fluvio-lacustrine sequence in this basin, which contains the Shanshenmiaozui mammalian fauna. Magnetite and hematite were identified as the main carriers for the characteristic remanent magnetizations. Magnetostratigraphic results show that the Shanshenmiaozui sedimentary sequence recorded the Brunhes chron, the Jaramillo subchron, and the late Matuyama chron. Stratigraphic correlation in terms of lithology, magnetic susceptibility and magnetic polarity sequences between the Shanshenmiaozui, Xiaochangliang and Dachangliang sections indicates that the Shanshenmiaozui mammalian fossil layer is younger than the Xiaochangliang and Dachangliang artefact layers, which have been previously estimated to be about 1.36 Ma. The age of the Shanshenmiaozui mammalian fossil layer at the bottom of the section is estimated to be about 1.2 Ma. The new magnetostratigraphy of the Shanshenmiaozui section provides useful constraints on lithostratigraphic and biostratigraphic correlations in the Nihewan Basin.